Feasibility and utility of transbronchial cryobiopsy in precision medicine for lung cancer: Prospective single‐arm study. Issue 7 (7th July 2020) - Udagawa, Hibiki; Kirita, Keisuke; Naito, Tomoyuki; Nomura, Shogo; Ishibashi, Masayuki; Matsuzawa, Reiko; Hisakane, Kakeru; Usui, Yuko; Matsumoto, Shingo; Yoh, Kiyotaka; Niho, Seiji; Ishii, Genichiro; et al.
Abstract: Cryoprobe is a novel transbronchial biopsy (TBB) tool that yields larger tissue samples than forceps. Pathological diagnosis and biomarker analysis, such as genetic alterations and programmed death‐ligand 1 (PD‐L1) expression, are paramount for precision medicine against lung cancer. We evaluated the safety and usefulness of cryoprobe TBB for lung cancer diagnosis and biomarker analysis. In this single‐center, prospective single‐arm study, patients suspected of having or diagnosed with primary lung cancer underwent cryoprobe TBB using flexible bronchoscopy after conventional forceps TBB from the same lesion. Cryoprobe TBB was performed in 121 patients. The incidence rate of severe bleeding and serious adverse events (4% [90% confidence interval: 2%‐9%]) was significantly lower than the expected rate (20% with 30% threshold, P  < 0.01). Combining both central and peripheral lesions, the diagnostic yield rate of cryoprobe samples was 76% and that of forceps samples was 84%. Compared with forceps TBB samples, cryoprobe TBB samples were larger (cryoprobe 15 mm 2 vs forceps 2 mm 2 ) and resulted in a larger proportion of definite histomorphological diagnosis (cryoprobe 86% vs forceps 74%, P  < 0.01), larger amounts of DNA extracted from samples (median: cryoprobe, 1.60 µg vs forceps, 0.58 µg, P  = 0.02) and RNA (median: cryoprobe, 0.62 µg vs forceps, 0.17 µg, P  < 0.01) extracted from samples, and tended to yield greater rates of PD‐L1 expression >1% (51% vs 42%). In conclusion, cryoprobe is a safe and useful tool for obtaining lung cancer tissue samples of adequate size and quality, which allow morphological diagnosis and biomarker analysis for precision medicine against lung cancer. Abstract : In this study, cryoprobe biopsy was performed in 121 patients. The incidence rate of severe bleeding and serious adverse events was 4%. Compared with forceps biopsy samples, cryoprobe biopsy samples were larger and resulted in a larger proportion of definite histomorphological diagnoses and larger amounts of DNA/RNA extracted from samples.